No effect of ovarian stimulation and oocyte yield on euploidy and live birth rates: an analysis of 12 298 trophectoderm biopsies. Issue 5 (29th April 2020) - Irani, M; Canon, C; Robles, A; Maddy, B; Gunnala, V; Qin, X; Zhang, C; Xu, K; Rosenwaks, Z
Abstract : STUDY QUESTION: Does ovarian stimulation affect embryo euploidy rates or live birth rates (LBRs) after transfer of euploid embryos? SUMMARY ANSWER: Euploidy rates and LBRs after transfer of euploid embryos are not significantly influenced by gonadotropin dosage, duration of ovarian stimulation, estradiol level, follicle size at ovulation trigger or number of oocytes retrieved, regardless of a woman's age. WHAT IS KNOWN ALREADY: Aneuploidy rates increase steadily with age, reaching >80% in women >42 years old. The goal of ovarian stimulation is to overcome this high aneuploidy rate through the recruitment of several follicles, which increases the likelihood of obtaining a euploid embryo that results in a healthy conceptus. However, several studies have suggested that a high response to stimulation might be embryotoxic and/or increase aneuploidy rates by enhancing abnormal segregation of chromosomes during meiosis. Furthermore, a recent study demonstrated a remarkable difference in euploidy rates, ranging from 39.5 to 82.5%, among young oocyte donors in 42 fertility centres, potentially suggesting an iatrogenic etiology resulting from different stimulation methods. STUDY DESIGN, SIZE, DURATION: This is a retrospective cohort study that included 2230 in vitro fertilisation (IVF) with preimplantation genetic testing for aneuploidy (PGT-A) cycles and 930 frozen-thawed single euploid embryo transfer (FET) cycles, performed in our centre between 2013 and 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 12 298 embryos were analysed for ploidy status. Women were divided into five age groups (<35, 35–37, 38–40, 41–42 and >42 years old). Outcomes were compared between different durations of stimulation (<10, 10–12 and ≥13 days), total gonadotropin dosages (<4000, 4000–6000 and >6000 IU), numbers of oocytes retrieved (<10, 10–19 and ≥20 oocytes), peak estradiol levels (<2000, 2000–3000 and >3000 pg/mL), and sizes of the largest follicle on the day of trigger (<20 and ≥20 mm). MAIN RESULTS AND THE ROLE OF CHANCE: Within the same age group, both euploidy rates and LBRs were comparable between cycles regardless of their differences in total gonadotropin dosage, duration of stimulation, number of oocytes harvested, size of the largest follicles or peak estradiol levels. In the youngest group, (<35 years, n  = 3469 embryos), euploidy rates were comparable between cycles with various total gonadotropin dosages (55.6% for <4000 IU, 52.9% for 4000–6000 IU and 62.3% for >6000 IU; P  = 0.3), durations of stimulation (54.4% for <10 days, 55.2% for 10–12 days and 60.9% for >12 days; P  = 0.2), number of oocytes harvested (59.4% for <10 oocytes, 55.2% for 10–19 oocytes and 53.4% for ≥20 oocytes; P  = 0.2), peak estradiol levels (55.7% for E2 < 2000 pg/mL, 55.4% for E2 2000–3000 pg/mL and 54.8% for E2 > 3000 pg/mL; P  = 0.9) and sizes of the largest follicle (55.6% for follicles <20 mm and 55.1% for follicles ≥20 mm; P  = 0.8). Similarly, in the oldest group (>42 years, n  = 1157 embryos), euploidy rates ranged from 8.7% for gonadotropins <4000 IU to 5.1% for gonadotropins >6000 IU ( P  = 0.3), from 10.8% for <10 days of stimulation to 8.5% for >12 days of stimulation ( P  = 0.3), from 7.3% for <10 oocytes to 7.4% for ≥20 oocytes ( P  = 0.4), from 8.8% for E2 < 2000 pg/mL to 7.5% for E2 > 3000 pg/mL ( P  = 0.8) and from 8.2% for the largest follicle <20 mm to 8.9% for ≥20 mm ( P  = 0.7). LBRs after single FET were also comparable between these groups. LIMITATIONS, REASONS FOR CAUTION: Although this large study (2230 IVF/PGT-A cycles, 12 298 embryos and 930 single FET cycles) demonstrates the safety of ovarian stimulation in terms of aneuploidy and implantation potential of euploid embryos, a multi-centre study may help to prove the generalisability of our single-centre data. WIDER IMPLICATIONS OF THE FINDINGS: These findings reassure providers and patients that gonadotropin dosage, duration of ovarian stimulation, estradiol level, follicle size at ovulation trigger and number of oocytes retrieved, within certain ranges, do not appear to significantly influence euploidy rates or LBRs, regardless of the woman's age. STUDY FUNDING/COMPETING INTEREST(S): No external funding was received and there are no competing interests to declare. TRIAL REGISTRATION NUMBER: N/A